2003
DOI: 10.1590/s1677-55382003000400002
|View full text |Cite
|
Sign up to set email alerts
|

Case selection and outcome of radical perineal prostatectomy in localized prostate cancer

Abstract: Radical prostatectomy continues to play a central role in the management of localized prostate cancer. The majority of patients diagnosed with prostate cancer will undergo radical prostatectomy. A decrease in the morbidity of this surgical procedure has been accomplished through an improved understanding of pelvic anatomy and a greater understanding of the natural history of prostate cancer. Recently, minimally invasive techniques have been applied to radical prostatectomy (laparoscopic prostatectomy) in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Holzbeierlein et al in 2003 confirmed that radical perineal prostatectomy offers outcomes similar to radical retropubic prostatectomy. Its advantages included decreased pain, blood loss, and convalescence [11]. In addition, it is the optimal approach for obese patients, patients with prior pelvic surgery, or patients with prior pelvic radiation.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Holzbeierlein et al in 2003 confirmed that radical perineal prostatectomy offers outcomes similar to radical retropubic prostatectomy. Its advantages included decreased pain, blood loss, and convalescence [11]. In addition, it is the optimal approach for obese patients, patients with prior pelvic surgery, or patients with prior pelvic radiation.…”
Section: Introductionmentioning
confidence: 65%
“…In similar populations of patients, RPP offered equivalent organ-confined, marginpositive and biochemical recurrence rates to RRP, while causing significantly less blood loss [9,10]. Holzbeierlein et al in 2003 confirmed that radical perineal prostatectomy offers outcomes similar to radical retropubic prostatectomy. Its advantages included decreased pain, blood loss, and convalescence [11].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Belt prepared a subsphincteric modification and Hudson a transsphincteric one. Dillon, Weldon, and Tavel also made further improvements [5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%